2000
DOI: 10.1597/1545-1569(2000)037<0348:saliit>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Speech and Language Issues in the Cleft Palate Population: The State of the Art

Abstract: State-of-the-art activity demands a look back, a look around, and, importantly, a look into the new millennium. The area of speech and language has been an integral part of cleft palate care from the very beginning. This article reviews the development and progression of our knowledge base over the last several decades in the areas of speech; language; anatomy and physiology of the velopharynx; assessment of velopharyngeal function; and treatment, both behavioral and physical, for velopharyngeal problems. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0
9

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(126 citation statements)
references
References 305 publications
(276 reference statements)
4
113
0
9
Order By: Relevance
“…Consistent with previous findings [27][28][29][30], most of children with CAD had the typical type of articulation in clefts in both the screening evaluations and formal articulation tests (Tables 2 and 3). Table 4 displays that 39 (93%) of the children with CP ± L had articulation disorders.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous findings [27][28][29][30], most of children with CAD had the typical type of articulation in clefts in both the screening evaluations and formal articulation tests (Tables 2 and 3). Table 4 displays that 39 (93%) of the children with CP ± L had articulation disorders.…”
Section: Discussionsupporting
confidence: 91%
“…Particularly in relation to speech, signs of velopharyngeal insufficiency (VPI), which is the inability of the soft palate to make contact with the upper throat wall to close off the nose during speech. Speech defects from VPI include hypernasality, nasal air escape, weak intraoral air pressure during oral sound production, and use of atypical places of production known as CAD or cleft characteristic articulation disorders [11,13]. CAD are generally developed from inadequate oral pressure for oral consonants caused by velopharyngeal insufficiency.…”
Section: Doi: 105372/1905-74150806347mentioning
confidence: 99%
“…The classmate sample is more than double that of affected children because we compared affected children to all of their matched controls on all grades with available ITP data (before and after switching school districts). This approach preserved the classmate sample composition when comparing academic achievement over multiple grades (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) or school levels instead of including classmate data only for overlapping grades with the affected child (which would include different classmates at different grades for children who switched school districts). Also, this comparison reduces potential biases from selective switching on the basis of the child' s academic performance and characteristics of the new school district.…”
Section: Study Samplementioning
confidence: 99%
“…2 Sequelae include infant feeding problems, recurrent otitis media, and speech difficulties. [3][4][5] Several studies have shown that children with isolated clefts have an increased incidence of learning problems and academic underachievement. 6 This work focused primarily on reading and, although there are exceptions, 7 most studies reported that affected children score lower than expected compared with test norms and unaffected controls.…”
mentioning
confidence: 99%
“…Estudos (PAMPLONA et al, 2012;BESSELL et al, 2013) Apesar de existirem métodos objetivos para a avaliação da fala como a avaliação aerodinâmica e análise acústica o julgamento perceptivo-auditivo é o método de avaliação considerado como "padrão ouro" para a caracterização das alterações de fala (GERRATT et al, 1993;KREIMAN et al, 1993;KENT, 1996;KUEHN;MOLLER, 2000;KUMMER et al, 2012;CHAPMAN et al, 2015). A avaliação perceptiva das alterações de fala, incluindo as AC, pode sofrer influência de vários fatores (SANTELMAN; SUSSMAN; CHAPMAN, 1999;GOOCH et al, 2001;HOWARD;HESELWOOD, 2002;HENNINGSSON et al, 2008), dentre estes destacam-se a experiência do avaliador em realizar o julgamento perceptivo-auditivo destas produções (GOOCH et al, 2001;OLSSON, 2004;BRUNNEGARD;LOHMANDER, 2007), bem como a seleção e qualidade das amostras de fala utilizadas durante o julgamento.…”
Section: Revisão De Literaturaunclassified